2006
DOI: 10.1111/j.1085-9489.2006.00080.x
|View full text |Cite
|
Sign up to set email alerts
|

SIMPLE mutation analysis in dominant demyelinating Charcot‐Marie‐Tooth disease: three novel mutations

Abstract: Charcot-Marie-Tooth disease type 1C (CMT1C) is caused by mutations in the small integral membrane protein of the lysosome/late endosome (SIMPLE). We analyzed the coding sequence of SIMPLE in DNA of 53 unrelated cases of dominant demyelinating CMT disease with no mutations in PMP22, GJB1, MPZ, EGR2, and NEFL genes. Four different missense mutations were observed in six families. The mutation Gly112Ser was found in two families confirming its frequent occurrence in SIMPLE mutations. Three novel mutations were al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
46
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 22 publications
6
46
0
2
Order By: Relevance
“…The Gly112Ser mutation in the LITAF gene detected in the CMT family may act in our patient at least in two independent ways. In the peripheral nerve, the mutated LITAF gene causes a typical course of mild peripheral demyelinating neuropathy seen in our proband's affected family members, and was previously described in other CMT1C patients harbouring Gly112Ser mutation [1,8,16,18].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The Gly112Ser mutation in the LITAF gene detected in the CMT family may act in our patient at least in two independent ways. In the peripheral nerve, the mutated LITAF gene causes a typical course of mild peripheral demyelinating neuropathy seen in our proband's affected family members, and was previously described in other CMT1C patients harbouring Gly112Ser mutation [1,8,16,18].…”
Section: Discussionsupporting
confidence: 72%
“…In all to-date reported CMT1C-affected patients harbouring the Gly112Ser mutation, a homogenous phenotype of mild slowly progressive demyelinating neuropathy was present without symptomatic central nervous system involvement [8,16,18].…”
Section: Introductionmentioning
confidence: 99%
“…Genetic studies have identified eight missense mutations in small integral membrane protein of lysosome/late endosome (SIMPLE) that cause autosomal dominant, demyelinating CMT type 1C (CMT1C) (Street et al, 2003;Bennett et al, 2004;Saifi et al, 2005;Latour et al, 2006;Gerding et al, 2009). SIMPLE, also known as lipopolysaccharide-induced TNF-a factor (LITAF), is a 161 amino acid protein that has been implicated in cytokine signaling (Moriwaki et al, 2001;Bolcato-Bellemin et al, 2004) and tumor suppression (Mestre-Escorihuela et al, Wang et al, 2009), but its precise cellular function remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in more than 30 genes cause CMT (4), and many more remain to be discovered. The demyelinating forms are the most common, and the genetic causes of most of these conditions have been discovered (5,6). Even though some of the genes associated with demyelinating forms of CMT are expressed in other cell types, the primary abnormality - demyelination - is caused by effects of the mutations in myelinating Schwann cells (7).…”
Section: Hsan1 One Of Many Hereditary Peripheral Neuropathiesmentioning
confidence: 99%
“…Even though some of the genes associated with demyelinating forms of CMT are expressed in other cell types, the primary abnormality - demyelination - is caused by effects of the mutations in myelinating Schwann cells (7). The axonal forms of CMT are less common, and their genetic causes remain unknown for the majority of affected patients (5,6). In most cases, expression of the mutant gene in the affected neurons likely produces an axonal neuropathy, but this has been experimentally demonstrated for only a few kinds.…”
Section: Hsan1 One Of Many Hereditary Peripheral Neuropathiesmentioning
confidence: 99%